Improved response time of thick liquid crystal device by using electrospun nanofiber. (2nd May 2017) - Duong, Toan Quoc; Kobayashi, Hiroaki; Inoue, Yo; Moritake, Hiroshi
Abstract: In this study, we report the improved response time of a thick nematic liquid crystal (LC) device by using an electrospun nanofiber (NF). We investigated the influence of NF characteristics including polymer material, NF volume ratio, and diameter, on the electrical characteristic of the NF/LC composite. A conventional LC device and a polymer-stabilized liquid crystal (PSLC) device were fabricated to compare their electrical characteristics with those of the NF/LC composite. The rise time, decay time, and threshold voltage of these LC devices are determined by measuring the dielectric permittivity. In comparison with the conventional LC device, the decay time of the NF/LC device is significantly improved. Compared with the PSLC device with the same thickness, the NF/LC device shows a lower threshold voltage while exhibiting the same decay time. Finally, we demonstrated the markedly improved response time of a THz phase shifter by using an NF/LC composite.